Retention and patient satisfaction with bar-clip, ball and socket and kerator attachments in mandibular implant overdenture treatment: An in vivo study - Nitish Varshney; Sumit Aggarwal; Shalabh Kumar; S P Singh (Wolters Kluwer Medknow Publications, 2019)
Aim: The aim of this in vivo study was to evaluate and compare the retention and patient satisfaction in implant supported mandibular overdenture with three different attachment system. Materials and Methods: After evaluation of prosthetic space, fifteen edentulous subjects received two implants in the inter-foramina region of the mandible and were divided into 3 groups with 5 subjects each, delayed loading protocol was followed in all the patients. The retention force and satisfaction level with the attachments at baseline and after 6 months was measured in a standardised way using retentive device and VAS questionnaire. The study was based on evaluation of retention and patient satisfaction. 15 subjects were included in the study. The results obtained were statistically analyzed using one-way ANOVA test, and multiple comparisons were carried out using the Bonferroni tests. Results: At the end of six months, the retention force and satisfaction level was higher in Group 3 (Kerator attachment) as compared to Group 1 (ball and socket attachment) and Group 2 (bar and clip attachment) and patient satisfaction was equal in groups 1, 2 and 3 but the total number of interventions is significantly higher in the attachment bar. Analysis of variance with repeated measures showed significant differences in retention force among the three attachment types. Conclusion: (1) Group 3 (kerator attachment) exhibit higher retentive capacities than Group 1 (ball and socket attachment) and Group 2 (bar and clip attachment). (2) patient satisfaction was higher in Group 3 (Kerator attachment) in compare to Group 1 (ball and socket attachment) and Group 2 (bar and clip attachment).